PENATAAN KAWASAN WISATA DENGAN PENDEKATAN ADAPTASI BENCANA TSUNAMI STUDI KASUS KAWASAN PANTAI PAAL, KABUPATEN MINAHASA UTARA - Judah Yosia Wanjoyo; Suryono Herlambang; B. Irwan Wipranata (Jurusan Arsitektur dan Perencanaan, 2022)
The Paal Beach area is one of the tourist areas that has great natural potential seen from the coastal landscape with white sand, underwater beauty, and the surrounding hills which add to the increasingly diverse tourist experience. However, it does not yet have adequate infrastructure, facilities and infrastructure. In addition, the great potential for tourism development on a national scale also needs to pay attention to the risk factors for disasters which are quite large, especially on the Paal coast which reaches a wave height of up to 8 meters so that it has vulnerability to tsunamis. Therefore, the main objective in this study is to identify the existing conditions in the Paal Beach Tourism Area at the macro, mezzo, and micro scope in various aspects to be a reference in the analysis process and make a proposal for a planning master plan concept with a tsunami disaster adaptation approach in the Coastal Tourism Area. However, Paal is still able to integrate the main characters on the beach and hills through accessibility, space utilization, infrastructure, and supporting facilities for tourism activities. This research is a qualitative and quantitative research. Qualitative data was obtained by conducting field surveys to locations and conducting interviews with related parties, while quantitative data was obtained by distributing questionnaires to visitors. The results of this study are in the form of a planning master plan concept with a tsunami disaster adaptation approach in the Paal Beach Tourism Area by integrating the main characters on the beach and hills through accessibility, space utilization, infrastructure, and supporting facilities for tourism activities. Keywords: Tourism Spatial Planning; Paal Beach; Tsunami Disaster Adaptation Approach Abstrak Kawasan Pantai Paal menjadi salah satu area wisata yang memilki potensi alami yang besar dilihat dari lansekap pesisir pantai dengan pasir yang putih, keindahan bawah laut, dan bukit – bukit di sekitarnya yang menambah pengalaman wisatawan yang semakin beragam. Akan tetapi kawasan ini belum memiliki infrastruktur, sarana dan prasarana yang memadai. Selain itu, potensi besar terhadap pengembangan wisata skala nasional juga perlu memperhatikan faktor resiko bencana yang cukup besar terutama pada pada pesisir Pantai Paal yang mencapai ketinggian gelombang hingga 8 meter sehingga memilki kerawanan terhadap tsunami. Tujuan utama dalam penelitian ini adalah mengidentifikasi kondisi eksisting pada Kawasan Wisata Pantai Paal pada lingkup makro, mezzo, dan mikro di berbagai aspek untuk menjadi acuan dalam proses analisis dan membuat usulan konsep masterplan perencanaan dengan pendekatan adaptasi bencana tsunami pada Kawasan Wisata Pantai Paal namun tetap dapat mengintegrasikan karakter utama pada pantai dan bukit melalui aksesbilitas, pemanfaatan ruang, infrastruktur, dan fasilitas pendukung untuk kegiatan wisata. Penelitian ini merupakan penelitian kualitatif dan kuantitatif. Data diperoleh dengan melakukan survey lapangan ke lokasi dan melakukan wawancara dengan pihak terkait, sedangkan untuk data kuantitatif diperoleh dengan penyebaran kuesioner ke pengunjung. Hasil dari penelitian ini berupa konsep masterplan perencanaan dengan pendekatan adaptasi bencana tsunami pada Kawasan Wisata Pantai Paal dengan mengintegrasikan karakter utama pada pantai dan bukit melalui aksesbilitas, pemanfaatan ruang, infrastruktur, dan fasilitas pendukung untuk kegiatan wisata.